Letter from Julia Morgan to William Randolph Hearst, March 20, 1924 - Julia Morgan::::::author:::; William Randolph Hearst::::::author::: (1924)
Letter originally written by Morgan to Hearst, and then subsequently sent back to Morgan with handwritten responses provided by Hearst